1995
DOI: 10.1023/a:1016200501563
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The gastrointestinal transit of multiple units (e.g., pellets), as determined by gamma scintigraphy, has been characterized by the application of statistical moments. Stomach emptying profiles can be described comprehensively by Mean Gastric Residence Time (MGRT) and Variance of Gastric Residence Time (VGRT) and caecum arrival data by Mean Caecum Arrival Time (MCAT) and Variance of Caecal Arrival Time (VCAT). This maximizes the data available, which is not the case when only described as 50% values. The statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The MRT is an important parameter to quantify the permanence of the drug in the bloodstream following a multiple dosing regimen [3336]. To the best of our knowledge, there are no studies that evaluated the influence of multiple dosing protocols regarding MNP in the bloodstream, which is the most common protocol for drug administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MRT is an important parameter to quantify the permanence of the drug in the bloodstream following a multiple dosing regimen [3336]. To the best of our knowledge, there are no studies that evaluated the influence of multiple dosing protocols regarding MNP in the bloodstream, which is the most common protocol for drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the MRT calculation takes into account the entire signal, regarding the three injections for G1 (three injections at a 35 min interval between them, with total data acquisition period of 105 min), and one single injection for G2 (also with a 105 min of acquisition interval). The MRT calculation is a well described method widely used to assess the pharmacokinetics regarding multiple dosing regimens [3335], and to quantify gastric emptying and gastrointestinal transit time [27, 36]. The MRT can be obtained according to Podczeck et al [36]:where I t  = ACB intensity signal at time t.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, model dependent estimates such as AUC and MGRT were also determined. Here, the parameter MGRT results from the application of statistical moments to the gastric emptying data (8). All calculations and graphical presentations were made in MS Excel 2003.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…3). All seven individual profiles from (20) were not included in the model building N number of volunteers enrolled in the fasted study, IND individual scintigraphic profile (number of profiles), G graphical presentation of mean scintigraphic data (number of volunteers), W water, OJ orange juice, N/A information not available, t 50 time for 50% of pellets remaining in stomach, t lag time when pellets started leaving the stomach, AUC area under the scintigraphic data curve, MGRT mean gastric residence time a The data were also presented in (8) b Size of the pellets without the coating c Two formulations tested on the same subject d Only the range of the parameter values was presented e Results of pellets of only this density were taken into account in statistic analysis and modeling f Coffee was also provided at 1.5 h g Only the data taken at upright position of volunteers were included h Only data based on the control study were enrolled process as the reported data were mostly sparse (infrequent data imaging). The profiles from (9), which were obtained after administration of pellets to subject NA, KI, SL, JE, VK, and JA were renumbered as profile A, B, C, D, E, and F, respectively.…”
Section: Selection Of Individual Profilesmentioning
confidence: 99%
See 1 more Smart Citation